2007
DOI: 10.1186/1475-2891-6-2
|View full text |Cite
|
Sign up to set email alerts
|

An increase in dietary n-3 fatty acids decreases a marker of bone resorption in humans

Abstract: Human, animal, and in vitro research indicates a beneficial effect of appropriate amounts of omega-3 (n-3) polyunsaturated fatty acids (PUFA) on bone health. This is the first controlled feeding study in humans to evaluate the effect of dietary plant-derived n-3 PUFA on bone turnover, assessed by serum concentrations of N-telopeptides (NTx) and bone-specific alkaline phosphatase (BSAP). Subjects (n = 23) consumed each diet for 6 weeks in a randomized, 3-period crossover design: 1) Average American Diet (AAD; [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 58 publications
5
157
5
Order By: Relevance
“…In our study, the ratio was clearly lower, on average 4, compared with the previously reported Polyunsaturated fat and bone mineral density R Järvinen et al Polyunsaturated fat and bone mineral density R Järvinen et al 8-10 (Weiss et al, 2005). In a clinical trial, both diets with linoleic:a-linolenic acid ratio of 1.6 and 3.5 resulted in significantly lower bone resorption markers than a diet with a ratio of 9.5, corresponding the average American diet (Griel et al, 2007). However, findings from recent prospective studies among the US citizens are controversial.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, the ratio was clearly lower, on average 4, compared with the previously reported Polyunsaturated fat and bone mineral density R Järvinen et al Polyunsaturated fat and bone mineral density R Järvinen et al 8-10 (Weiss et al, 2005). In a clinical trial, both diets with linoleic:a-linolenic acid ratio of 1.6 and 3.5 resulted in significantly lower bone resorption markers than a diet with a ratio of 9.5, corresponding the average American diet (Griel et al, 2007). However, findings from recent prospective studies among the US citizens are controversial.…”
Section: Discussionmentioning
confidence: 83%
“…Much of the research has emanated from animal models fed diets with n-3 LCPUFA far in excess of that in the human diet [157]. Nonetheless, randomised clinical trials [39] and cohort studies [38,41,44] support an important role for LCPUFA in human bone health. At this time, more data is required to incorporate n-3 LCPUFA into guidelines for the attainment and maintenance of bone mass in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Some human studies indicate that PUFAs can increase bone formation, affect peak bone mass in adolescents [38] and reduce bone loss as measured using bone mineral densitometry [39]. In contrast, some of the studies in humans did not find any effect on bone markers [40] while some showed reduction in bone loss by measuring deoxypyridinolines and N-telopeptide of Type I collagen in the urine [8,38,39,41]. Two studies found a positive correlation between monounsaturated fat in the diet and bone density [42,43].…”
Section: Figurementioning
confidence: 99%
“…Therefore, they tend not exacerbate the OA disease process [17]. No change in the plasma alkaline phosphatase activity was recorded in adult rats maintained on high dietary N-3 [18]. However, N-3 have also been noted to decrease [19], or increase [20,21] the bone formation process.…”
Section: Discussionmentioning
confidence: 93%